1989
DOI: 10.1021/bi00440a036
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the 9-methyl group of retinal inhibits signal transduction in the visual process. A fourier transform infrared and biochemical investigation

Abstract: The photoreaction of opsin regenerated with 9-demethylretinal has been investigated by UV-vis spectroscopy, flash photolysis experiments, and Fourier transform infrared difference spectroscopy. In addition, the capability of the illuminated pigment to activate the retinal G-protein has been tested. The photoproduct, which can be stabilized at 77 K, resembles more the lumirhodopsin species, and only minor further changes occur upon warming the sample to 170 K (stabilizing lumirhodopsin). UV-vis spectroscopy rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
171
3
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(201 citation statements)
references
References 20 publications
24
171
3
1
Order By: Relevance
“…The displacement of the chromophore was reduced by introducing twists along the single bonds C 14 OC 15 (40°), C 10 OC 11 (20°), and C 8 OC 9 (20°); whereas, the C 12 OC 13 twist was kept constant at 30°and the C 6 OC 7 angle was reduced to 20°to load the 5-methyl group against 8-H (3, 37). These twist assignments agree well with Raman and FTIR data (5,32). CCC bends of the chromophore in this intermediate (accompanied by CCCC torsions), leading to protein-retinal steric interactions, are thought to represent the main contribution to energy storage in the batho intermediate (7,43,44).…”
Section: Scheme IIIsupporting
confidence: 84%
See 3 more Smart Citations
“…The displacement of the chromophore was reduced by introducing twists along the single bonds C 14 OC 15 (40°), C 10 OC 11 (20°), and C 8 OC 9 (20°); whereas, the C 12 OC 13 twist was kept constant at 30°and the C 6 OC 7 angle was reduced to 20°to load the 5-methyl group against 8-H (3, 37). These twist assignments agree well with Raman and FTIR data (5,32). CCC bends of the chromophore in this intermediate (accompanied by CCCC torsions), leading to protein-retinal steric interactions, are thought to represent the main contribution to energy storage in the batho intermediate (7,43,44).…”
Section: Scheme IIIsupporting
confidence: 84%
“…In batho, the newly introduced twist in the chromophore complicates calculation of the counterion-PSB distance. However, in bsi and lumi the chromophore twists have largely relaxed (31,32) and we assume that the relative shifts (numbers in parentheses in Table 1) of the max values, in proceeding from the dark state to bsi and from bsi to lumi, can be interpreted qualitatively in terms of counterion Ϫ PSB Intermediate spectra require the kinetic scheme to be known, and the bleach (the amount and Gaussian shape of the photolyzed sample determined in a separate experiment, data not shown) must be added back to the difference spectra (23). distance (24).…”
Section: Scheme IIImentioning
confidence: 99%
See 2 more Smart Citations
“…Fax: (91) (80) 3341683. E-mail: sv@mbu.iisc.ernet.in **E-mail: laxman@mbu.iisc.ernet .in dopsin (bR) and Rhodopsin (Rh) associated with their function indicate the involvement of the peptide bond at the Pro residues as 'hinges' [27][28][29]. The findings of Strader et al, on Pro to Ser mutation in fl-adrenergic receptor had suggested the involvement of P323 in a receptor processing event such as folding [30].…”
Section: Introductionmentioning
confidence: 99%